Associations between vitamin D receptor gene polymorphisms and ankylosing spondylitis in Chinese Han population: a case–control study. Issue 7 (July 2016) - Cai, G.; Zhang, X.; Xin, L.; Wang, L.; Wang, M.; Yang, X.; Li, X.; Xia, Q.; Xu, S.; Ding, C.; Pan, F.
Abstract Summary We assessed whether the vitamin D receptor gene polymorphisms (FokI, BsmI, ApaI, and TaqI) were associated with ankylosing spondylitis (AS) in a Chinese Han population. The TaqI polymorphism G allele was a risk factor in AS susceptibility. Introduction Previous studies have found that serum vitamin D levels are declined in patients with AS. The present study aims to evaluate the role of vitamin D receptor (VDR) gene polymorphisms in AS susceptibility in a Chinese Han population. Methods Four single nucleotide polymorphisms (SNPs) in the VDR gene (FokI (rs2228570), BsmI (rs1544410), ApaI (rs7975232), and TaqI (rs731236)) were genotyped by the improved multiplex ligase detection reaction (iMLDR) method in 620 AS patients and 620 geographically and ethnically matched healthy controls. Haplotypes were constructed after linkage disequilibrium (LD) analysis. Results Statistically significant difference was only found in the TaqI polymorphism between AS patients and controls. The TaqI polymorphism G allele was higher in AS group than that in controls (OR [95 % CI] = 1.624 [1.122–2.352], χ 2  = 6.705, P  = 0.006). Linkage disequilibrium has been detected in TaqI and BsmI polymorphisms (D′ = 0.87, r 2  = 0.70). Two novel haplotypes (H1: AC and H2: GT) were significantly associated with the risk of AS, and they play protective and risk roles in AS morbidity, respectively. Conclusions The VDR gene TaqI polymorphism G allele may be a risk factor in AS susceptibility.